Experimental Study on Bearing Capacity of Alkaline Activated Granular Asphalt Concrete Columns on Soft Soils - Erdawaty Erdawaty; Tri Harianto; A. B. Muhiddin; Ardy Arsyad (Salehan Institute of Higher Education, 2020)
In civil engineering, alternative materials showed rapid progress. Asphalt derived from Buton Island in Indonesia, also known as Asbuton, was located in the limestone bedrock. A large deposit of Asbuton could guarantee the supply of alternative construction materials. In that regard, Asbuton performance as an alternative material to several subjects needs to be analyzed. Therefore, this study was conducted to analyze Asbuton’s behavior as a filler in a floating column model as a soft soil improvement concept. Asbuton added to sand and gravel mixture as filler and waterglass as a binder. CBR samples were tested to acquire the optimum composition with varied curing days namely 0, 3, and 7 days, following ASTM D-1883, followed by a compressive column model test which was based on ASTM D-2166. Finally, the column applied to the soft soil layer to be tested in a loading test, and the results are then compared for each composition. The results showed that the granular material's composition including Asbuton, the waterglass content, and the curing period significantly affect the engineering properties of the artificial column. The results revealed that the granular column with Asbuton with the addition of waterglass could increase soil’s load capacity and reduce the settlement of soft soils. Doi: 10.28991/cej-2020-03091623 Full Text: PDF